Blended Learning Assessment Instrument For Elementary School - Meta Yuliyana; Rochmiyati Rochmiyati; Dina Maulina (research, training and philanthropy institution Natural Aceh, 2021)
This article was written as the stage of designing a blended learning assessment instrument model in elementary schools. This study aims to identify an assessment model that accommodates the realm of cognitive learning. The design phase of this research is based on the ADDIE model framework. The research population is all students of class V SDN 1,2, and 3 Karanganyar, the research sample is class V students at SDN 2 Karanganyar who have implemented blended learning. The data analysis technique used in this research is the descriptive data analysis technique. Based on the author's hypothesis, the stages of the development model that can be used based on the results of the analysis of assessment instruments for blended learning, there are three types of assessment, namely self-assessment, peer assessment, and teacher assessment. This triangle model is expected to accommodate the realm of learning in the implementation of blended learning assessment.